(untitled) (Research, Society and Development, 2021)
Objective: To carry out a bibliographic survey and reports on the increase in cases of Yellow Fever, Chickungunya, Dengue and Zika after the rupture of the Mariana and Brumadinho dams (Minas Gerais). Methodology: A bibliographic, epidemiological study was carried out with articles, reports and search in academic platforms and bulletins from the Ministry of Health in order to associate the increase in cases according to their location according to the period after the rupture. Results: There was an evident increase in cases of arboviruses right after the rupture of the dams in areas affected by the impact and proximity. This may be the result of the movement of people and animals after the tragedies, because with the degradation of the area, people were directly and indirectly affected, those who were directly affected had their houses destroyed by mud and those who were affected in a way may have left the city in search of alternatives for improvement. There is also a change in the local food chain, some populations increase and others decrease, mosquito populations increase and migrate to other more populous areas in search of food, thus being a factor in the spread of diseases. Conclusion: It was observed that in the period from 2015 to 2016 the cases of CHIKV were those that grew the most in Brazil, with an increase of almost 10x, of Yellow Fever and Dengue having an increase of more or less 3x. Zika cases begin to be reported in 2015, so it is not possible to determine whether there has been a significant increase.